2008
DOI: 10.1111/j.1099-0860.2008.00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Understanding of Factors Influencing Early Years Professionals’ Practice of Consultation with Young Children

Abstract: Recent Government agendas in England highlight a need to involve children in policy and service design, provision and evaluation of services they use or which affect them. While consultation with older children has become more common, this is not the case for younger children. This article reports on a study exploring the current practice and experiences, perceptions and views of a sample of early years professionals with regard to consultation with young children. A theoretical model is presented which sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Adults act as a barrier to children's participation (Davies and Artaraz 2009;Lopez et al 2012). Children confirm that adults normally do not respect them.…”
Section: Children's Participation In Disaster Risk Reductionmentioning
confidence: 96%
“…Adults act as a barrier to children's participation (Davies and Artaraz 2009;Lopez et al 2012). Children confirm that adults normally do not respect them.…”
Section: Children's Participation In Disaster Risk Reductionmentioning
confidence: 96%
“…In the context of this study, participation is understood as a child's right to be involved in their learning and sharing responsibility and power for decision making about matters that affect their lives (Davies and Artaraz, 2009;Hill et al, 2004;Article 12 (UNCRC) 1989). Participation is underpinned by progressive steps involving listening to and consultation with children (Shier, 2001;Lancaster, 2003) which are crucial in building a pedagogical space that contributes to children's learning and well-being where they can make independent choices, share responsibility and make sense of their learning (Clark, 2005(Clark, , 2004Nutbrown, 1996).…”
Section: An Emancipatory Theoretical Frameworkmentioning
confidence: 99%
“…Sinclair (2004) ''has suggested there has not been enough evaluation of the outcomes of participation and it is important that researchers write in greater depth and more transparently about the participative processes in young people's research'' (cited in Franks, 2009, p. 9). Furthermore, while children with special education needs and disabilities have been involved to varying degrees in research*as respondents/participants within data collection activities (Gordon, 2003;Henry, 2002;NICCY, 2008b;Ravet, 2007;Slevin, Truesdale-Kennedy, McConkey, Fleming, & Livingstone, 2008;Taylor, 2007) and as researchers in the design and conduct of the research (Educable, 2000;Kelly, McColgan, & Scally, 2000)*these children (Curtin & Murtagh, 2007;Franklin & Sloper, 2009;Stein, 2009) and very young children (Davies & Artaraz, 2009) are less likely to be represented, in the published literature in this area, than their older and non-disabled peers (Hill et al, 2004). Furthermore, participative research activity reported to date has documented less with regard to involving children and young people in decision-making about research design and instrumentation than with regard to data collection and analysis.…”
mentioning
confidence: 98%